A Caching Algorithm for Information Centric Network Using Fuzzy Logic - Torregoza, Mark Lorenze R.; Dadios, Elmer P. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The internet today has evolved from information superhighway to a household necessity that offers more than just information. Nowadays, the internet serves a lot of purpose. It is a tool for not just information but entertainment that offers music, graphics and videos that is available for downloading or streaming. It has also evolved to be a medium of communication that offers a global link from people around the globe. From emails, short message services and even voice communication, the internet has all of these to offer. The former information superhighway is today a social media platform that is open to all ages to all variety of users. With this development, it is logical to think that the current internet network scheme should also be subjected to evolution. The emerging Information Centric Network is quite a good fit to the future of internet. The idea to be concerned to the content that is to be accessed more than the identity of the one accessing the content is tailor-fit to the current application of internet. In a nutshell, ICN requires node with caching functionality. An effective caching algorithm is a great help to attain the very purpose of ICN which is to come up with an efficient network. Meanwhile, fuzzy logic, which has proven to be effective in control or optimization applications, can also be applied in improving caching functionality of ICN. This paper explores the application of fuzzy logic to the caching algorithm that can be used to further improve current information centric networks. The results were obtained from hypothetical data because this is just to prove that fuzzy logic can be applied in the caching dynamics of Information Centric Network.